Duodenal adenomatosis in Japanese patients with familial adenomatous polyposis. (April 2014) - Maehata, Yuji; Esaki, Motohiro; Hirahashi, Minako; Kitazono, Takanari; Matsumoto, Takayuki
Abstract : Duodenal adenomatosis is the most frequent extracolonic manifestation of familial adenomatous polyposis (FAP), and duodenal cancer has been assumed to be the second most significant cause of death in patients with the disease. To stratify the risk of duodenal cancer, Spigelman's classification was proposed for the staging of duodenal adenomatosis. According to Western guidelines, patients with stage IV of the classification are candidates for prophylactic duodenectomy. Since our institutional experience disclosed only 2% of duodenal or ampullary cancers among 130 patients with FAP, and because most duodenal adenomatosis remains unchanged under endoscopic surveillance, it seems likely that aggressive endoscopic or surgical removal is unnecessary for most FAP patients with duodenal adenomatosis. In the present article, we demonstrate our data and present our strategy for duodenal adenomatosis of FAP.